Perbedaan Corporate Governance Dan Financial Ratios Pada Perusahaan Distressed Dan Non-Distressed - Laura Calvina, Yanti (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to know the difference between financial distressed firms and non-financial distressed firmsthat listed in Bursa Efek Indonesia for period 2015-2017. This research used 42 manufacturing companies, which 14 companies are financial distressed firms and 28 companies are non-financial distressed firms, with purposive sampling method with total 84 data and using non-parametic statistic Mann Whitney. The results indicates that there is a difference in liquidity and leverage between financial distressed firms and non-financial distressed firms. But, there is no difference in institutional ownership and the size of board director between financial distressed firms and non-financial distressed firms.